A textbook of integrated engineering physics - Chakrabarty, Amal Kr (Chhaya Prakashani, 2011)
A textbook of integrated engineering physics / Chakrabarty, Amal Kr. -- Kolkata: Chhaya Prakashani, 2011 530 C426 No. of Copies : 2